2019
DOI: 10.2147/cmar.s215107
|View full text |Cite
|
Sign up to set email alerts
|

<p>Incident cancer risk in dipeptidyl peptidase-4 inhibitor-treated patients with type 2 diabetes mellitus</p>

Abstract: Objective It is known that patients with diabetes are susceptible to cancer development due to long-standing diabetic conditions. This study aimed to investigate new-onset cancer risk associated with dipeptidyl peptidase-4 (DPP-4) inhibitors as compared to metformin, the first-line antidiabetic agent with promising anticancer activity, in patients with type 2 diabetes mellitus (T2DM). Methods A retrospective cohort study of adult T2DM patients was performed at a tertiar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Regulatory authorities imposed a warning on the risk of pancreatitis for all available DPP-4i. This decision is motivated by a supposed increase in risk of new cases of pancreatitis, suggested by pharmacovigilance reports [1,2] and some metanalyses of randomized trials [21][22][23], but not confirmed by the majority of available observational studies [6][7][8][9][10][11][12]. Notably, both the European Medicines Agency and Food and Drug Administration issued a warning on pancreatitis, without considering a history of pancreatitis as a formal contraindication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regulatory authorities imposed a warning on the risk of pancreatitis for all available DPP-4i. This decision is motivated by a supposed increase in risk of new cases of pancreatitis, suggested by pharmacovigilance reports [1,2] and some metanalyses of randomized trials [21][22][23], but not confirmed by the majority of available observational studies [6][7][8][9][10][11][12]. Notably, both the European Medicines Agency and Food and Drug Administration issued a warning on pancreatitis, without considering a history of pancreatitis as a formal contraindication.…”
Section: Discussionmentioning
confidence: 99%
“…pancreatitis and pancreatic cancer for both the DPP-4i sitagliptin and the GLP1 receptor agonist exenatide; however, pharmacovigilance reports could overestimate the actual risk, because of over-reporting of unexpected adverse events with newer therapies. However, several observational studies failed to detect any association between incretin-based therapies (i.e., DPP-4i and GLP1 receptor agonists) and pancreatic disease [6][7][8][9][10][11][12], with the exception of only one survey detecting an increased risk [13]. The interpretation of retrospective observational data is problematic, since confounders cannot be entirely accounted for in adjusted models.…”
Section: Introductionmentioning
confidence: 99%
“…Anticoagulant users were then classified into two cohorts of either warfarin or NOAC users, in accordance with their primary anticoagulant therapy that lasted for ≥30 consecutive days; NOAC agents include rivaroxaban, apixaban, dabigatran, and edoxaban. Those patients with a history of both treatments for an equivalent length of time, which was defined as the treatment duration not differing by ≥50% of each other’s prescribed days, were excluded from further analysis, 18 leading to two mutually exclusive user groups. Predetermined variables included patient demographics, such as age and gender, cancer sites, Khorana scores, comorbidities, Charlson comorbidity index (CCI) scores, exposure to chemotherapy with high thrombotic risk, including tamoxifen, thalidomide, lenalidomide, cisplatin, fluorouracil, L-asparaginase, bevacizumab, 17 along with concomitant medications with bleeding risk, such as antiplatelets, nonsteroidal anti-inflammatory drugs (NSAIDs), corticosteroids, and parenteral anticoagulants.…”
Section: Methodsmentioning
confidence: 99%
“…These data suggested that DPP-4 inhibitors induce existing microtumor/precancerous cell visibility rather than inducing de novo carcinogenesis. On the other hand, a propensity-matched cohort study of T2DM patients in Korea represented that DPP-4 inhibitor treatment did not increase the risk of pancreatic and thyroid cancer compared to metformin treatment [ 117 ].…”
Section: The Influence Of Dpp-4 Inhibitors On Cancer: Clinical Evidencementioning
confidence: 99%